Affective Mathematical Disposition Profile of First-Year Prospective Mathematics Teachers: A Mixed Methods Study - Dirgantoro, Kurnia Putri Sepdikasari; Soesanto, Robert Harry (Edumatica : Jurnal Pendidikan Matematika, 2026)
Mathematics learning involves not only conceptual mastery but also affective dispositions that shape engagement and professional development. This study explores the affective domain of mathematical disposition among first-year prospective mathematics teachers and examines its alignment with indicators of early professional readiness. An explanatory mixed-methods design was employed involving 24 first-year students from a teacher education program in Indonesia. Quantitative data were collected using a validated affective mathematical disposition questionnaire, and differences between high- and low-disposition groups were analysed using the Mann–Whitney U test. Follow-up semi-structured interviews were conducted with six participants to explore professional motivations, conceptions of teaching competence, and professional initiative. The results indicate that usefulness and worthwhileness were the strongest affective aspects, while mathematical self-concept emerged as comparatively weaker. Statistically significant differences were found between high- and low-disposition groups across all affective aspects. Qualitative findings suggest that higher affective disposition aligns with stronger intrinsic motivation, more integrated conceptions of teaching competence, and more deliberate professional initiative. These findings provide preliminary evidence that affective mathematical disposition may play a contributory role in the early development of professional teacher identity